Partisipasi Masyarakat terhadap Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan di Desa Kauditan II Kecamatan Kauditan Kabupaten Minahasa Utara - yanno . dien (Universitas Sam Ratulangi, 2013)
ABSTRACTYanno Dien. The societyâ€™s participation in the â€œPNPM Mandiri Perdesaan atKauditan II Village, North Minahasa Regencyâ€. Under guidance of Welson M.Wangke as chairman and Benu Olfie L.S and Celcius Talumingan as members.The objective of the study in to determine society participation from the planningstages to the evaluation stage in the program â€œPNPM Mandiri Perdesaan at Kauditan IIVillage, North Minahasa Regencyâ€.Data used in this research are the primary data and secondary data. Primary data inobtained through direct interviews with a sample of respondents, to be guided with a list ofquestions prepare in advance. While secondary data in derived from relevant agencies,namely the village office Kauditan II. Data are analyzed descriptively and presented intabular form.The results showed that societyâ€™s participation in the â€œPNPM Mandiri Perdesaan atKauditan II Villageâ€ can be seen from the following measurement variables: the presence inthe activities at the planning meetings and provide suggestions / proposals andconsumption, the presence in each activity at the stage of implementation of activities andparticipation given at the stage of implementation of such personnel, funding, equipmentand consumption as well as the evaluation stage presence, asking opinions andconsumptionâ€™s participation.Based on the results of the study it can be concluded that the societyâ€™s in the â€œPNPMMandiri Perdesaan at Kauditan II Villageâ€ from the planning phase to the implementationphase of the evaluation can be Categorized as very active. It is need the guidance and thesupervision continuously from the goverment to support active participation by hisinvolving better in every development program and community development in order tocreate community empowerment.